2022
DOI: 10.1111/are.15985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different stocking densities and carbon:nitrogen ratios on growth, body composition and production performance of Labeo rohita (Hamilton, 1822) spawn in biofloc based‐nursery system

Abstract: total finfish production (FAO, 2020). Still, higher production can be achieved, but the unavailability of fry as a result of high mortality during the nursery rearing phase has been one of the major impediments in expanding its production. Generally, nursing of carp from spawn to fry stage is undertaken in small earthen ponds. With proper nursery management, where survival of 30%-40% of fry is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In the present study, a lower stocking density of SD3 resulted in improved growth performance as compared to other groups. Te results agree with the fndings of Dey et al [17] who observed enhanced growth of Labeo rohita spawn in terms of fnal length, fnal weight, and SGR at a lower stocking density (1, 2, and 3 spawn L −1 ) than at a higher stocking density (4 and 5 spawn L −1 ) in biofoc systems. Impaired growth of goldfsh larvae with an increase in the stocking density in the BFT system was recorded by Besen et al [8].…”
Section: Efect On Survival and Growth Parameters Of Gibelion Catlasupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, a lower stocking density of SD3 resulted in improved growth performance as compared to other groups. Te results agree with the fndings of Dey et al [17] who observed enhanced growth of Labeo rohita spawn in terms of fnal length, fnal weight, and SGR at a lower stocking density (1, 2, and 3 spawn L −1 ) than at a higher stocking density (4 and 5 spawn L −1 ) in biofoc systems. Impaired growth of goldfsh larvae with an increase in the stocking density in the BFT system was recorded by Besen et al [8].…”
Section: Efect On Survival and Growth Parameters Of Gibelion Catlasupporting
confidence: 92%
“…As bacteria need about 20 units of carbon per unit of nitrogen assimilated [27], in this study, it is confrmed that a C/N ratio of 20 : 1 favored biofoc promotion which acts as a supplemental food source available 24 hrs [33,[64][65][66]. Te improvement in growth of catla spawn at C/N 20 could be associated with the presence of adequate natural proteinlipid source and other nutrients at any time as observed for Carassius auratus larvae at C/N ratios of 20 and 25 : 1 and Labeo rohita spawn at C/N 15 and 20 [17], whereas the insignifcant diference in the C/N 10 and 15 groups might indicate the limited number of prey production as reduction in organic carbon addition can slow down the formation of foc as observed with lower foc volume at a lower C/N ratio in the present study [29,67], or consumption of biofoc does not contribute to growth of the fsh [12]. Biofoc is known to improve feed utilisation of fsh by supplementing essential amino acids, vitamins, lipids, and minerals and stimulates digestive enzyme activity resulting in improved digestion of nutrients in the fsh gut [68].…”
Section: Efect On Survival and Growth Parameters Of Gibelion Catlamentioning
confidence: 56%
See 2 more Smart Citations